Synergy of Social and Managerial Strategies in 21st-Century Inclusive Differentiated Learning - Hasana, Imroatun; Afriani, Nita; Yusuf, Maulana; Hamidah, Nida; Setiana, Pragiwati; Safitri, Rizky Ulfa Rini; Kamalya, Farhah Millaty; Gresinta, Efri (IJOSMAS, 2024)
Learning in the 21st century demands an approach that is responsive to the diversity of learners. Differentiated learning is a strategic solution to accommodate diverse needs, interests, and abilities, and to create an inclusive learning environment. This article analyzes the synergy between social and managerial aspects in the implementation of differentiated learning, emphasizing four main elements: differentiation of content, process, product, and learning environment. This approach is supported by educational theories such as Gardner's multiple intelligences and Piaget's cognitive development, which emphasize the importance of adjusting learning methods based on learner characteristics. Differentiated learning also supports the implementation of a flexible Independent Curriculum, the use of technology, and the integration of 21st-century skills (4C). However, its implementation faces challenges such as limited resources, time management, and resistance to change. Through teacher training support, collaboration between school management, teachers, and parents, and a culture-based approach, differentiated learning can reduce educational disparities. This strategy has been shown to increase student engagement, motivation, and achievement, while creating relevant, inclusive, and equitable learning experiences in the era of globalization.